Embodied ethics: Some common concerns of religion and business - Leahy, John T. (Journal of business ethics, 1986)
De George's understanding of theology is limited to one of five commonly recognized models of theology, the orthodox model. This model is vulnerable to De George's criticisms. When religious ethics operates out of the revisionist model of theology, however, his criticisms lose their sting. Revisionist religious ethics, moreover, can make a fruitful contribution to business ethics. Such a religious ethic acknowledges the embodiment dimension of business activities, it complements philosophical analysis with the practice of moral discernment, and it recognizes irony as an active component in decision-making.